Accuracy and precision of point of care testing in pragmatic critically ill patients setting - Durongbhandhu, Tharathorn; Soisuwan, Tharntip; Soisuwan, Pornhathai (Thai Journal of Emergency Medicine, 2023)
Introduction Point of care testing (POCT) refers to laboratory tests performed outside of the traditional laboratory setting (Central lab). One advantage of POCT is that it can be completed quickly, and doctors can perform the tests themselves after receiving brief training. This can reduce the time needed to make treatment decisions. However, the accuracy and precision of the POCT for patients with critical illness, particularly in a real-world emergency setting, are still a matter of debate. Objectives To study the accuracy and precision of POCT in patients with critical illness in the emergency department Method Retrospective observational study collected laboratory data of emergency patients in Chonburi Hospital from 1 January-31 December 2020. The inclusion criteria were 15-year-old patients or above who had critically ill problems (e.g., cardiac arrest, shock, and sepsis) and need emergency treatment. Blood samples were analyzed by POCT (Blood Analyzer, Abbot, Cartridge CHEM8) and the central laboratory room at the same time for evaluation of Sodium (Na), Potassium (k), Bicarbonate (HCO3), Blood Urea Nitrogen (BUN), Creatine (Cr) and Hematocrit (Hct) respectively. The laboratory value from POCT and the central laboratory room were analyzed by Bland-Altman analysis (B.A. plot) and the results were presented with correlation, mean difference (MD), and level of agreement (LOA) Results 100 patients were enrolled in the study. The majority of them were male (66%). The average age was 56.6 years with a standard deviation of 17.3%. The majority of illnesses were related to cardiac arrest (67%). POCT and the central lab’s correlation coefficients were between 0.80 and 0.94. It is a strong positive correlation. Na has MD 0.53 with LOA -7.66,8.72 mEq/L, K has MD -0.10 with LOA -2.30,2.10 mEq/L, HCO 3 has MD -3.74 with LOA -11.13, 3.65 mEq/L, BUN has MD -3.30 with LOA -27.62, 21.02 mg/dl, Cr has MD -0.26 with LOA -1.20, 0.68 mg/dl and Hct has MD -0.56 with LOA -10.30,9.18% respectively. K had the lowest MD that lines between its LOA, it was only 93% of the total MD. Conclusion POCT strongly correlated with the Central lab. But assessing by agreement with the central lab, POCT reveals good accuracy, but poor precision, especially K, HCO 3 , and Hct. So, Critically ill patients’ treatment decisions should be based mainly on their clinical information.